Geometry of the Carotid Artery and Its Association With Pathologic Changes in a Chinese Population - Cui, Yiyao; Lv, Xiaoshuo; Wang, Feng; Kong, Jie; Zhao, Hao; Ye, Zhidong; Si, Chaozeng; Pan, Lin; Liu, Peng; Wen, Jianyan (Frontiers in Physiology, 2020)
Objectives: Carotid artery geometry influences blood flow disturbances and is thus an important risk factor for carotid atherosclerosis. Extracellular matrix (ECM) and yes-associated protein (YAP) expression may play essential roles in the pathophysiology of carotid artery stenosis, but the effect of blood flow disturbances of carotid bifurcation location on the ECM is unknown. We hypothesized that carotid artery anatomy and geometry are independently associated with the ECM and YAP expression. Methods: In this cross-sectional study, 193 patients were divided into two groups: an asymptomatic group (n=111) and a symptomatic group (n=82), symptomatic patients presenting with ischemic attack, amaurosis fugax, or minor non-disabling stroke. For all subjects before surgery, carotid bifurcation angle and internal artery angle were measured with computed tomography angiography (CTA), and laminar shear stress was measured with ultrasonography. After surgery, pathology of all plaque specimens was analyzed using hematoxylin and eosin (HE) staining and Movat special staining. Immunohistochemistry was performed to detect expression of YAP in a subset of 30 specimens. Results: Symptomatic patients had increased carotid bifurcation angle and laminar shear stress compared to asymptomatic patients (P<0.05), although asymptomatic patients had increased internal carotid angle compared to symptomatic patients (P<0.001). Relative higher bifurcation angles were correlated with increased carotid bifurcation, decreased internal angle, and decreased laminar shear stress. For each change in intervertebral space or 1/3 of vertebral body height, carotid bifurcation angle changed 4.76°, internal carotid angle changed 6.91°, and laminar shear stress changed 0.57 dynes/cm2. Pathology showed that average fibrous cap thickness and average narrowest fibrous cap thickness were greater in asymptomatic patients than symptomatic patients (P<0.05). Expression of proteoglycan and YAP protein in symptomatic patients were higher than in asymptomatic patients (P<0.001), while collagen expression was lower in symptomatic patients than asymptomatic patients (P<0.05). Conclusions: Geometry of the carotid artery and position relative to cervical spine might be associated with ECM and YAP protein expression, which could contribute to carotid artery stenosis.